Effectiveness of Culturally-Focused Batterer Counseling for African American Men in Pittsburgh, Pennsylvania, 2001-2004 - Gondolf, Edward W. ([Verlag nicht ermittelbar], 2008)
This study used an experimental clinical trial to test the effectiveness of culturally-focused batterer counseling against conventional cognitive-behavioral counseling in African American men. A total of 503 men, including all African American men mandated by the domestic violence court in Pittsburgh, Pennsylvania, to batterer counseling between November 2001 and May 2004, were randomly assigned to one of three counseling options: culturally-focused counseling in an all African American group, conventional counseling in an all African American group, or conventional counseling in a racially mixed group. All three counseling options required a minimum of 16 weekly group sessions. At program intake, the men completed a background questionnaire, the Short Michigan Alcoholism Screening Test (SMAST) and the Racial Identity Scale (RAIS), contained in Part 1, Men's Intake Questionnaire Data. The men later completed a survey of past experiences of violence, contained in Part 2, Men's Past Violence Survey Data. The men were interviewed once at five months after program intake about their impressions of and ratings of the counseling. Results of those interviews are in Part 3, Men's Five-Month Follow-up Data. A female partner was interviewed for 399 of the male subjects at program intake. Their responses are contained in Part 4, Women's Background Data. Female partners (both initial victims and new partners) were interviewed at 3, 6, 9, and 12 months after the initial interview at the time of the men's program intake (Parts 5-8). The follow-up interviews asked about the women's relationship status, abusive behavior and its circumstances, help seeking, and additional intervention.